Sustainable food systems in the context of the Common Agricultural Policy reform – legal aspects - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2020)
The focus of this article was at a preliminary assessment of whether the proposed assumptions of the Common Agricultural Policy for 2021–2027 could be considered conducive to the objectives of sustainable food systems included in the European Commission's “From farm to fork” strategy. In the author's opinion, the assumptions of sustainable food systems contained in this document correspond to some objectives of the Common Agricultural Policy included in the Treaty on the Functioning of the European Union. The final assessment whether the new common agricultural policy will bring effects from the point of view of building sustainable food systems requires making a reference not only to the future legal regulation which will apply in the next financing perspective, but also to the effects of its application. A radical change in the directions of the Common Agricultural Policy and implementation of sustainable development objectives may lead to a confrontation and competition of agricultural income support instruments with those for environmental protection including climate protection, at the expense of the latter.